2022
DOI: 10.3389/fendo.2022.1060309
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between hair metabolites, air pollution exposure and gestational diabetes mellitus: A longitudinal study from pre-conception to third trimester

Abstract: BackgroundGestational diabetes mellitus (GDM) is a metabolic condition defined as glucose intolerance with first presentation during pregnancy. Many studies suggest that environmental exposures, including air pollution, contribute to the pathogenesis of GDM. Although hair metabolite profiles have been shown to reflect pollution exposure, few studies have examined the link between environmental exposures, the maternal hair metabolome and GDM. The aim of this study was to investigate the longitudinal relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…Hair samples were cut into three segments (each segment 3cm long). Previous studies have demonstrated that utilizing a 3 cm segmentation of the same hair strand is proficient in discriminating between pregnancy trimesters ( 20 , 21 ). Thus, the first segment (0-3 cm) represented the third trimester, and the next 0.5 cm hair segment was discarded.…”
Section: Methodsmentioning
confidence: 99%
“…Hair samples were cut into three segments (each segment 3cm long). Previous studies have demonstrated that utilizing a 3 cm segmentation of the same hair strand is proficient in discriminating between pregnancy trimesters ( 20 , 21 ). Thus, the first segment (0-3 cm) represented the third trimester, and the next 0.5 cm hair segment was discarded.…”
Section: Methodsmentioning
confidence: 99%
“…Significant heterogeneity exists between studies, including differences in sample type, timing of sample collection and sample size, making comparison between studies, and therefore establishment of meaningful conclusions, difficult. Diet, pharmacological treatment and environmental factors ( 48 ) also influence metabolite abundance, as well as genetic and epigenetic factors ( 49 ), further confounding comparability of findings. Metabolomic findings discussed in this review are summarized in Table 1 .…”
Section: Subsectionsmentioning
confidence: 99%
“…For this reason, this specimen can be a good alternative for metabolomic studies, providing a broader view of the metabolic profile. Thus, in the last five years, hair samples have been widely used to study pregnancy complications, such as pre-eclampsia [ 127 ], fetal growth restriction [ 128 ], gestational T2DM [ 129 ], and diet restrictions [ 130 ]. Additional clinical investigations include the search for biomarkers in cervical cancer [ 131 ] and Alzheimer’s disease [ 132 , 133 ] and the monitoring of chronic conditions such as androgenetic alopecia [ 134 ] and baldness [ 135 ].…”
Section: Underexplored Specimens In Clinical Metabolomicsmentioning
confidence: 99%
“…Metabolite extraction is performed with or without alkaline hydrolysis, using NaOH 4 mol L −1 [ 139 ] or, more frequently, KOH 1 mol L −1 , followed by neutralization with H 2 SO 4 (3 mol L −1 ) [ 127 , 128 , 131 ]. Proteins are usually precipitated by the addition of pure methanol [ 125 , 129 , 134 , 135 ], methanol/phosphate saline buffer (PBS) [ 132 , 133 , 140 ], or methanol/water/acetone (1:1:1, v / v / v ) [ 141 ]. In order to increase extraction performance, bench mills [ 142 , 143 ], ultrasound [ 132 , 133 ], and vortex [ 128 , 139 ] have been applied.…”
Section: Underexplored Specimens In Clinical Metabolomicsmentioning
confidence: 99%